Collaboration between ambulance services and primary care: a scoping review protocol - Carina Elmqvist; Elin-Sofie Forsgärde; Anders Svensson; Cecilia Fagerström; Mats Holmberg; Linda Ljungholm; Ann-Therese Hedqvist (BMJ Open)
Introduction Making decisions about the appropriate level of care is a significant challenge for healthcare professionals, especially when older patients present with diffuse symptoms. Collaboration between ambulance services and primary care may promote a comprehensive understanding of patient needs. However, such collaboration remains limited, potentially leading to lower care quality and higher costs. There is a need to understand how collaboration can be effectively implemented. This scoping review aims to explore existing models of collaboration between ambulance services and primary care, identifying their characteristics, outcomes and current research gaps.Methods and analysis This scoping review will follow the methodological framework proposed by Arksey and O’Malley, supplemented with recommendations from the Joanna Briggs Institute Handbook for Scoping Reviews. A comprehensive literature search will be conducted in PubMed, CINAHL, Web of Science and Scopus. In addition, Google Scholar, Overton, SwePub and the Swedish national library database Libris will be searched for relevant grey literature. The review will include studies published from January 2014 to the present. Data will be analysed descriptively, with findings categorised by collaboration models and patterns identified through inductive analysis to address the research questions. The review will apply the Preferred Reporting Items for Systematic Review and Meta-Analysis extension for Scoping Reviews to present the results.Ethics and dissemination This review is the first stage of an overarching research study to develop a model for extended collaboration between ambulance services and primary care (the ECAP project). Results will be disseminated through peer-reviewed publications, conference presentations and sharing with ambulance services and primary care stakeholders to inform practice and policy. This scoping review protocol has been registered on the Open Science Framework (https://osf.io/nrkm5/). No participants will be involved at this stage, and the selected literature is publicly available, so no ethical approval will be required for this scoping review.